The effect of organizational support for creativity on innovation and market performance: the moderating role of market dynamism. Issue 4 (30th November 2021) - Baccarella, Christian V.; Maier, Lukas; Meinel, Martin; Wagner, Timm F.; Voigt, Kai-Ingo
Abstract : Purpose: Recent technological and social changes have challenged manufacturing firms to remain competitive in increasingly dynamic markets. A way of facing these challenges is to foster organizational structures that encourage creativity. Although the general importance of organizational creativity for market success is undeniable, few studies on manufacturing firms have provided a nuanced view of how this relationship is affected by firm-external factors (e.g. different levels of market dynamism) and whether and how this leads to greater market success. Design/methodology/approach: This research uses survey data from 255 chief executive officers (CEOs) and top managers of manufacturing firms in Germany. The authors performed different regression analyses to test for direct, mediation, moderation and moderated mediation effects. Findings: The findings show that, in highly dynamic markets, organizational support for creativity indeed helps manufacturing firms to remain competitive by positively influencing firms' innovation performance, which subsequently results in improved market performance. By contrast, in markets with low dynamism, organizational support for creativity has no impact on firms' innovation and market performance. Research limitations/implications: From a theoretical perspective, this study introduces market dynamism as a novel, so-far underexplored firm-external factor that moderates the relationship between organizational support for creativity and innovation and market performance. This research thus enhances the understanding of the dynamics of organizational creativity and its effects on innovation and market performance in an organizational context of manufacturing firms. Practical implications: In general, this research emphasizes the importance of establishing a creativity-supporting environment to enhance innovation and market performance. Most importantly, this relationship depends on whether firms are active in highly dynamic or stable markets. Managers should thus consider the level of (future) market dynamism when making decisions about creativity-supporting work environments. Originality/value: This research provides novel insights into how organizational support for creativity influences innovation and market performance in the manufacturing industry and introduces market dynamism as an important moderating factor.